Real-option Valuation and Cross-sectional Analysis for Pharmaceutical Companies：Evidence from China Market - Tian, Zonghua (2020)
With the worldwide impact of Covid-19, more attention has been put on pharmaceutical companies and new drug research and development projects. This research attempts to prove the existence of real option value of pharmaceutical companies in the context of China as the additional value from managerial flexibility and potential profitability, taking existing theoretical and empirical studies as basis. With respect to the empirical analysis, the binomial tree model is applied on the growth option of 100 sample pharmaceutical companies and the result shows that most of them have positive real option value. As an academic innovation, the study is also expected to reveal the linkage between real option value and some relevant company characteristics. A cross-sectional regression is constructed and applied on the real option value along with the robustness tests. The regression demonstrates that leverage level, operation ability, management characteristics, company size and expected profitability have effects on option value. The result enlightens that companies could increase the added value of managerial flexibility from the perspective of trade-off on leverage level, improving operation ability, paying more attention on R&D and extending company size, which may have profound influence on the future development of pharmaceutical industry.